Die Afrikaanse koerantopskrif : 'n semantiese beskouing - De Villiers, L. E. S.(Lourens Erasmus Smit) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M.A.) -- Universiteit van Stellenbosch, 1961.